New lapsiine jumping spiders from Ecuador (Araneae: Salticidae) - Maddison, Wayne P. (Zootaxa, 2006)
Two new genera and three new species of salticid spider from eastern Ecuador are described, belonging to a group informally called "lapsiines". The new genus Galianora is based on Galianora sacha, new species, and also contains Galianora bryicola, new species. The new genus Thrandina includes the single new species Thrandina parocula. These genera share the ancestral salticid traits, rare among neotropical salticids, of a tarsal claw on the female palpus and a median apophysis on the male palp. Galianora is distinguished from other lapsiines by the round tegulum with peripheral embolus. The strikingly large posterior median eyes of Thrandina are unique among New World salticids.